On (p, q)-Opial type inequalities for (p, q)-calculus - ALP, Necmettin; SARIKAYA, Mehmet Zeki (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper, we establish some (p, q)-Opial type inequalities and generalization of (p, q)-Opial type inequalities. Mathematics Subject Classification (2010): 26D10, 26D15, 81S25.